2010
DOI: 10.1051/0004-6361/200811486
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of energetic electrons with anisotropic distributions in solar flares

Abstract: Aims. The paper aims are to simulate steady-state distributions of electrons beams precipitating in collisional and Ohmic losses with pitch angle anisotropy into a flaring atmosphere with converging magnetic field and to apply these to the interpretation of HXR photon spectra, directivity and polarization observed for different photon energies and flare positions on the solar disk. Methods. Summary approximation method is applied to a time-dependent Fokker-Planck equation by splitting the temporal derivative e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 51 publications
(88 reference statements)
0
57
0
4
Order By: Relevance
“…However, the n-distribution is a parametric distribution that describes well only the bulk of the distribution function during flares . In particular, the ndistributions do not contain the high-energy tail observed commonly during flares (e.g., Asai et al 2009;Veronig et al 2010;Zharkova et al 2010;Guo et al 2011). This high-energy tail then dominates the bremsstrahlung spectrum at the X-ray wavelengths and corresponding photon energies of tens of keV.…”
Section: Non-maxwellian Bremsstrahlung Spectrummentioning
confidence: 98%
See 2 more Smart Citations
“…However, the n-distribution is a parametric distribution that describes well only the bulk of the distribution function during flares . In particular, the ndistributions do not contain the high-energy tail observed commonly during flares (e.g., Asai et al 2009;Veronig et al 2010;Zharkova et al 2010;Guo et al 2011). This high-energy tail then dominates the bremsstrahlung spectrum at the X-ray wavelengths and corresponding photon energies of tens of keV.…”
Section: Non-maxwellian Bremsstrahlung Spectrummentioning
confidence: 98%
“…In solar physics, on which we focus here, departures from the equilibrium Maxwellian distribution occur every time particles are accelerated, e.g., in flares, where high-energy tails Appendix A is available in electronic form at http://www.aanda.org are ubiquitous (Petkaki & MacKinnon 2007Zharkova & Gordovskyy 2006;Veronig et al 2010;Zharkova et al 2010Zharkova et al , 2011Fletcher et al 2011;Holman et al 2011). Apart from that, departures from Maxwellian distributions can occur at low plasma densities if there are strong gradients of temperature and density, i.e., in the transition region (e.g., Owocki & Scudder 1983;Ljepojevic & MacNiece 1988;Scudder 1992;Pinfield et al 1999;, in conditions where the mean energy can change (Collier 2004), i.e., during plasma heating.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray observations with, e.g., RHESSI (Lin et al 2002) show that the flare electron distribution is composed of a plasma bulk, which is usually considered to be Maxwellian, and a high-energy tail, approximated with a power-law distribution (e.g., Brown 1971;Lin & Hudson 1971;Holman et al 2003;Brown et al 2008;Krucker & Lin 2008;Asai et al 2009;Warmuth et al 2009;Veronig et al 2010;Kurt et al 2010;Zharkova et al 2010;Guo et al 2011). The ionization equilibrium and synthetic spectra for the Maxwellian electron distribution are widely known (e.g., CHIANTI, Landi et al 2006;Dere et al 2009), but there are only few papers on the influence of the high-energy tail on the ionization equilibrium and the line spectra.…”
Section: Introductionmentioning
confidence: 99%
“…However, existing models of particle acceleration and precipitation considering not only collisional but other energyloss mechanisms unavoidably report anisotropic particle distributions which vary significantly with precipitation depth (for example, see distribution functions in Zharkova et al 2010a, hereafter Paper I). Fleishman & Melnikov (2003a, 2003b have shown that the pitch-angle anisotropy of accelerated particles, even if it is unable to support a coherent wave amplification, can change significantly the emission intensity (up to orders of magnitude) and polarization (the sign of circular polarization).…”
Section: Introductionmentioning
confidence: 99%